Simultaneous extraction, separation, isolation and identification of endogenous components from Etlingera elatior by pressurized matrix solid-phase dispersion using liquid chromatography-mass spectrometry - Ge, Liya (2021)
From the analytical chemistry point-of-view, an ideal sample preparation method should be simple, rapid, automatic, selective, precise, exhaustive, reproducible and protect the analyte-of-interest from degradation. In this study, a novel sample preparation method, named pressurized matrix solid-phase dispersion (p-MSPD) extraction was developed for simultaneously extracting, separating, purifying, isolating, and analyzing endogenous components in a solid sample matrix. Etlingera elatior, a traditional medicinal plant known as the torch ginger, was applied as a sample matrix to evaluate the p-MSPD process. The entire extraction, separation, isolation, fractionation and detection were performed automatically with a commercial LC-MS system. The novel method was satisfactorily applied for the preparation of real samples without optimization, which had the ability to selectively isolate pure compounds from the solid sample matrix for further NMR analysis. Therefore, the method is recommended for quality control of traditional medicines, research efforts when sample amounts are limited, and laboratories that have ordinary LC-MS instrumentation.